Pemilihan Presiden dan Wakil Presiden Secara Langsung Persperktif Politik dan Hukum Tata Negara - Moh. Mahfud MD (Universitas Islam Indonesia, 2004)
The 2004 national election will give us such different discourse about our national leader July2004. This is the time to that the people will choose their own president and the vice president. This is, can be seen as a good achievement from the perspective of constitutional law. By choosing their national leader directly, the can determine who will be responsible to run the government in the following five years. The weakness of the old presidential election is that the aspiration of representatives may different from the people aspiration, as a result, people will have a president who actually they don’t want. Through direct presidential election, not only the president will be more legitimated, but also, more national stability will be gained.